The experience of non-conveyance following emergency medical service triage from the perspective of patients and their relatives: A qualitative study. (January 2021) - van Doorn, Silvie C.M.; Verhalle, Ruud C.; Ebben, Remco H.A.; Frost, Donna M.; Vloet, Lilian C.M.; de Brouwer, Carin P.M.
Abstract: Background: As many as 25% of all Dutch ambulance emergency service assignments result in non-conveyance of the patient to the hospital. Little is known about how patients and their relatives experience being left at home by an ambulance nurse after an acute request for medical help. Aim: To gain insight into the experience of patients and their relatives with a high urgency request for ambulance assistance that results in non-conveyance, with the ultimate goal of offering adequate follow-up. Method: A qualitative design based on semi-structured interviews with fifteen patients and seven relatives, conducted between September and November 2018. Results: Four themes emerged from the thematic analysis: Fear as the prominent emotion, four components of confidence in decision-making, different consequences and coping between patient and relative(s) over time and the perceived need for evaluation afterwards. Conclusion: The experience after non-conveyance has several phases in which fear, reassurance, confirmation (for relatives) and shame (for patients) follow each other throughout the care process. Complex interpersonal skills of ambulance nurses congruent with the concept of person-centred care can modulate this impact. These findings offer starting points for the optimisation of training programmes within the ambulance care sector.